Design of Few-Mode Fibers for Mode-Division Multiplexing Transmission - Motoki Kasahara (IEEE Photonics Journal, 2013)
We investigate the fiber parameters that meet the design conditions for low bending loss and an effectively few-mode operation on few-mode fibers with a step-index profile and a W-shaped refractive index profile for mode-division multiplexing transmission. We also clarify the limits of effective area enlargement and the difference of the effective index while satisfying the design conditions.